2021
DOI: 10.3390/app11177921
|View full text |Cite
|
Sign up to set email alerts
|

Octacalcium Phosphate Bone Substitute (Bontree®): From Basic Research to Clinical Case Study

Abstract: Bone grafts used in alveolar bone regeneration can be categorized into autografts, allografts, xenografts, and synthetic bones, depending on their origin. The purpose of this study was to evaluate the effect of a commercialized octacalcium phosphate (OCP)-based synthetic bone substitute material (Bontree®) in vitro, in vivo, and in clinical cases. Material characterization of Bontree® granules (0.5 mm and 1.0 mm) using scanning electron microscopy and X-ray diffraction showed that both 0.5 mm and 1.0 mm Bontre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…These are demineralized bovine bone materials (DBBM) coated with OCP or Bonarc TM (Toyobo Co. Ltd., Osaka, Japan), which is a mixture of OCP and collagen. However, unlike these products, which are not fully composed of Ca-and P-containing apatites, the recently introduced OCP bone graft Bontree ® is fully composed of apatite compounds with 80 wt.% OCP and 20 wt.% HA [9]. Therefore, to our knowledge, this is the first clinical study on maxillary sinus grafts using a pure OCP-based synthetic bone substitute.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are demineralized bovine bone materials (DBBM) coated with OCP or Bonarc TM (Toyobo Co. Ltd., Osaka, Japan), which is a mixture of OCP and collagen. However, unlike these products, which are not fully composed of Ca-and P-containing apatites, the recently introduced OCP bone graft Bontree ® is fully composed of apatite compounds with 80 wt.% OCP and 20 wt.% HA [9]. Therefore, to our knowledge, this is the first clinical study on maxillary sinus grafts using a pure OCP-based synthetic bone substitute.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recent developments in mass production technology at room temperature, which does not require a sintering process, have opened up the possibility of clinical applications with improved physical properties and an inherently high osteogenic capacity of OCP. Our previous studies have demonstrated the efficacy and safety of bone regeneration using this commercialized biomimetic OCP synthetic bone substitute material (Bontree ® ; HudensBio Co., Gwangju, Korea) in preclinical and clinical studies [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The field of bone graft substitutes is crowded, but the holy grail has yet to be found. Therefore, despite the challenges to OCP, based on the encouraging results presented by Hamada et al [2] and other results in dental reconstructive surgery [4][5][6], a careful stepwise approach to clinical trials could be used in orthopaedics. The trials would likely be initiated by an institution working on critical research and development or a commercial company interested in adding to the field of bone graft substitutes.…”
Section: How Do We Get There?mentioning
confidence: 99%
“…Granular, rather than blockish, scaffolds (<2 ​mm) are used in clinical dentistry because their defect sizes in bone are usually small [ [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] ]. Macroporous granules are more favorable than dense granules (DGs) for the rapid ingrowth of bone [ [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] ].…”
Section: Introductionmentioning
confidence: 99%